2003
DOI: 10.1002/ajhb.10114
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in growth and physical abilities in trained and untrained girls 10–17 years of age

Abstract: The purpose of the present study was to assess the age differences in growth characteristics and physical abilities of physically active adolescent girls and to compare them to corresponding data for girls nonactive in sport. The cross-sectional study was carried out on 643 Estonian girls, 10-17 years of age, who were regularly training track and field, and 902 nonactive girls. The organized physical activity of the studied girls consisted of lessons in the school curriculum (2 x 45 minutes per week) for both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 14 publications
4
7
1
2
Order By: Relevance
“…The relationship between PA and motor performance corroborates the findings of most studies that report a positive association between PA and muscular strength and endurance as well as overall physical fitness, particularly in the standing broad jump (Lennox et al, 2008; Loko et al 2003; Wrotniak et al, 2006), medicine ball throw (Loko et al, 2003), push-ups (Lennox et al, 2008, Tovar et al, 2008) and isometric hand-dynamometry (Tovar et al, 2008). Different results were obtained by Hands et al (2009), who found no significant associations between PA and performance in standing broad jump, curl-ups, hand dynamometry and ball throw.…”
Section: Discussionsupporting
confidence: 84%
“…The relationship between PA and motor performance corroborates the findings of most studies that report a positive association between PA and muscular strength and endurance as well as overall physical fitness, particularly in the standing broad jump (Lennox et al, 2008; Loko et al 2003; Wrotniak et al, 2006), medicine ball throw (Loko et al, 2003), push-ups (Lennox et al, 2008, Tovar et al, 2008) and isometric hand-dynamometry (Tovar et al, 2008). Different results were obtained by Hands et al (2009), who found no significant associations between PA and performance in standing broad jump, curl-ups, hand dynamometry and ball throw.…”
Section: Discussionsupporting
confidence: 84%
“…5B). Power (standing long jump) in children with CMT1A was lower than age-equivalent norms at all ages, 26,29,39 and endurance (6-min walk test) was similar to published norms up to 11 years of age, 28 but it was lower than unaffected age-equivalent adolescents. 23 Walking Ability.…”
Section: Figuresupporting
confidence: 80%
“…Functional power was evaluated by standing long jump, whereby each child jumped horizontally forward as far as possible by taking off and landing with both feet. 29 The distance from the start line to the heel of the closest foot was recorded in centimeters (cm). Three trials were recorded and averaged for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…São vários os estudos existentes na literatura que referem associações significativas e positivas do tempo despendido na atividade física com a prestação em habilidades motoras fundamentais, nomeadamente no lançamento da bola (Fisher et al, 2005;Loko, Aule, Sikkut, Ereline, & Viru, 2003). Pelo contrário, não foram observadas associações da prática desportiva dos familiares com a prestação do lançamento.…”
Section: Resultados Domínio Biológico E Prestação De Lançamentounclassified